2012
DOI: 10.1007/s10459-012-9390-z
|View full text |Cite
|
Sign up to set email alerts
|

A latent growth model suggests that empathy of medical students does not decline over time

Abstract: Empathy is a relevant attribute in the context of patient care. However, a decline in empathy throughout medical education has been reported in North-American medical schools, particularly, in the transition to clinical training. The present study aims to longitudinally model empathy during medical school at three time points: at the entrance, final of pre-clinical phase and at the beginning of clinical training. Data collected with the adaptation to Portuguese of the Jefferson Scale of Physician Empathy (stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 31 publications
8
88
2
7
Order By: Relevance
“…Other authors published the data in this study. [18][19][20] The study population consisted of students belonging to the courses from the first to fifth year of the undergraduate degree program of Dentistry of eighteen Dental Faculties in six countries in Latin America (Dominican Republic, Costa Rica, Panama, Colombia, Argentina and Chile) (n total = 4407). [19][20][21] The Jefferson Scale of Physician Empathy (JSPE), the Spanish version for medical students (S), adapted and validated (for cultural form and content), specially for dental students in all the countries studied by criterion of judges, was applied to all students.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other authors published the data in this study. [18][19][20] The study population consisted of students belonging to the courses from the first to fifth year of the undergraduate degree program of Dentistry of eighteen Dental Faculties in six countries in Latin America (Dominican Republic, Costa Rica, Panama, Colombia, Argentina and Chile) (n total = 4407). [19][20][21] The Jefferson Scale of Physician Empathy (JSPE), the Spanish version for medical students (S), adapted and validated (for cultural form and content), specially for dental students in all the countries studied by criterion of judges, was applied to all students.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21] The primary and original data from the empathy levels within the course of each university examined were analyzed by the Cronbach's alpha test (reliability by internal consistency); the sum of the primary data score, obtained using the scale previously mentioned, were initially analyzed by the Kolmogorov-Smirnov normality test (K-S) in both types and to the Homoscedasticity Levene test and the effect size was measured by the Hedges (g). [18][19][20][21][22] The means of academic years, from first to fifth, in each of the universities were obtained from the aforementioned works [18][19][20] and tested for polynomial regression to determine the type of curve an analysis of variance sequentially. In addition, the regression equation was estimated and the coefficient of determination (R 2 ), were adjusted and unadjusted, associated with the estimated curve …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the article by Magalhães et al (2012) in a recent issue of Medical Teacher that assessed empathy in medical students with the Jefferson Scale of Physician Empathy and found that personality traits are weak or moderate predictors of empathy.…”
Section: Dear Sirmentioning
confidence: 99%